Analisis Perhitungan Timbulan Sampah Rumput di Area Perusahaan Migas - Nasywa Khalisah Pieter; Syadzadhiya Qothrunada Zakiyayasin Nisa' (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Oil and gas companies generally have large green areas as part of fulfilling environmental and aesthetic obligations in industrial areas. Routine maintenance such as grass cutting produces organic waste that needs to be managed efficiently to prevent negative environmental impacts. This study aims to calculate the generation of grass waste in oil and gas company areas by comparing two methods: direct weighing and sampling methods. The direct weighing method is carried out by collecting and weighing the results of the cutting in a limited area, while the sampling method involves taking samples from several representative points and extrapolating the results to the entire area. The results showed that the average grass waste generation was 0.286 kg/m². With an area of ​​around 1,000 m², the total generation is estimated to reach 286 kg. Both methods have proven to complement each other: direct weighing provides precise data, while the sampling method allows for efficient estimation for larger areas. This data can be used as a basis for planning more adaptive, effective, and sustainable grass waste management, including the use of waste as organic compost that has economic value and is environmentally friendly.